2004
DOI: 10.1677/erc.0.0110069
|View full text |Cite
|
Sign up to set email alerts
|

Management of risk of breast carcinoma in postmenopausal women.

Abstract: Breast carcinoma is the most frequent tumor in the female population. Many factors can influence the risk of breast cancer; some of them, such as old age and breast cancer 1/2 (BRCA1/BRCA2) gene mutations, are associated with a fourfold increase in risk. A previous diagnosis of atypical ductal or lobular hyperplasia or having a first-degree relative with a carcinoma are factors associated with a twoto fourfold increase in risk. A relative risk between 1 and 2 is associated with longer exposure to endogenous ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
5

Year Published

2005
2005
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 95 publications
0
14
0
5
Order By: Relevance
“…As a consequence of the differences between the M4 and M1 forms of VDR, bone mineral density has been shown to be higher in women harbouring the SNP that is associated with the M4 form [5,12,[16][17][18]. Bone mineral density has been associated with an increased risk of breast cancer [19][20][21][22][23][24] and this may explain the over-representation of this form of the receptor in the breast cancer patients diagnosed under the age of 51 years. This is especially important in younger women since in older women there is generally a reduced production of cholecalciferol in the skin in association with a reduction in the levels of estrogen and consequently decreased metabolic activation of vitamin D and expression of VDR.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence of the differences between the M4 and M1 forms of VDR, bone mineral density has been shown to be higher in women harbouring the SNP that is associated with the M4 form [5,12,[16][17][18]. Bone mineral density has been associated with an increased risk of breast cancer [19][20][21][22][23][24] and this may explain the over-representation of this form of the receptor in the breast cancer patients diagnosed under the age of 51 years. This is especially important in younger women since in older women there is generally a reduced production of cholecalciferol in the skin in association with a reduction in the levels of estrogen and consequently decreased metabolic activation of vitamin D and expression of VDR.…”
Section: Discussionmentioning
confidence: 99%
“…Other kinds of medications such as hormone therapy might, however, contribute to the latter observation. [36][37][38][39][40] Also, long-term usage of oral contraceptives would be compatible with the observed reduced risk of ovarian cancer. 41 MS patients in Denmark are recommended a diet rich in fruit and vegetables, and sparse in animal fat, 42 factors which might have a preventive effect on several cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Two separate studies, Breast Cancer Detection Demonstration Project [64] and the Canadian National Breast Screening Study [65] have shown that women with more than 75% increased breast density on the mammography have an approximately fivefold increase in the risk of developing breast carcinoma over women with less than 5% increased breast density. Both pre-and postmenopausal nulliparous women, as well as thinner women have, in general, an increased breast density [66] and therefore they may be at an increased risk for developing breast cancer. Nulliparity and high breast density seem to act synergistically since the breast cancer risk goes up to sevenfold when they are both present in a person [67].…”
Section: Other Breast Cancer Risk Factorsmentioning
confidence: 99%
“…in atomic bomb survivals, historically treated children for reduction of the thymus or repeated fluoroscopies for treatment of tuberculosis, and more recently, treatment of women for Hodgkin's disease) has been demonstrated to increase the risk of breast carcinoma [6,66]. The risk is dose-dependent and decreases gradually over time, therefore the modern screening mammography, which delivers a very low dose of radiation (200-400 mrad), has a considerable benefit-risk ratio [66].…”
Section: Other Breast Cancer Risk Factorsmentioning
confidence: 99%